A Theological Study of the Good Shepherd in the Letters of I, II Timothy, and Titus and Its Relevance for Pastoral Ministry in the Church Today - Sinaga, Mangiring (PT ARRUS Intelektual Indonesia, 2025)
A growing church requires servants called shepherds who carry out their ministry to the congregation. The pastor plays an important role in carrying out leadership as a leader given by God and someone who is called to be a shepherd. In carrying out his ministry, various problems often arise in the congregation. The purpose of writing this scientific paper is the importance of understanding the pastoral ministry in the letters I, II Timothy and Titus as well as pastoral in the church, and finding its relevance for pastoral ministry in the church today. The research method is Library Research in the form of an exposition of Paul's Letters to Timothy and Titus and a field research method through the distribution of questionnaires to 250 members of the congregation at the Bethel Indonesia Taman Modern Church as respondents. The writing limitation refers to pastoral leadership according to letters I, II Timothy and Titus. The results of this study state that the three hypotheses are not proven true, the study shows that 86.19% of respondents agree with the contents of the questionnaire, where the understanding of church members regarding pastoral ministry in letters I, II Timothy and Titus is low, while the level of pastoral service in the church is also low, and the level of relevance of pastoral service in letters I, II Timothy and Titus for pastoral service in the church today is low.